Mathematical modeling for the management of the carrying capacity of aquaculture enterprises in lakes and reservoirs - Bueno, Guilherme Wolff; Bureau, Dominique; Skipper-Horton, James Owen; Roubach, Rodrigo; Mattos, Flávia Tavares de; Bernal, Francisco Ernesto Moreno (Pesquisa Agropecuaria Brasileira, 2017)
Flooded areas of reservoirs and artificial lakes have been increasingly used for fish production; however, the waste generated by aquaculture has become a concern for the sustainable development of this activity. One of the main strategies adopted by management and regulatory agencies is the use of hydrodynamic models that calculate the carrying or nutrient load capacity of a particular water body and the effect of fish farming. These models are precise in the development of optimal strategies for feeding and waste calculation. This review paper addresses this topic and describes the methodology developed for the analysis and simulation of the carrying capacity for fish production, based on the integration of the Fish‑PrFEQ nutritional bioenergetic model and the hydrodynamic model of Dillon & Rigler. This methodology allows evaluating the real contribution of aquaculture waste and assists in the planning and management of aquaculture in these aquatic environments, besides enabling and encouraging producers and the aquaculture industry to use fish food with better nutritional quality and lower environmental impact.